EPR STUDY OF ORGANICALLY-GROWN VERSUS GREENHAOUSE STRAWBERRIES - CSILLAG, I.; DAMIAN, G. (Studia Universitatis Babeș-Bolyai Physica, 2016)
EPR spectroscopy was used to characterize changes in main paramagnetic components (Fe3+, free radical, Mn2+) and antioxidant capacity of two types of strawberries (grown in the greenhouse and in natural conditions). The results of studied samples show the interpretable differences between the analyzed samples, which may be consequences of different types of biochemical processes involved in the growth and maturation of fruits depending on the environmental conditions in which they are grown.